Evaluasi Performa Heat Exchanger Menggunakan Software Aspen HYSYS di Central Gathering Station "X" Plant Operations "Y" Pertamina Hulu Rokan - Helianty, Sri; Luthfi, Alif; Wijaya, Deni (Journal of Bioprocess, Chemical and Environmental Engineering Science, 2025)
The Rokan Block is one of Indonesia's largest oil producers. It is managed by PT Pertamina Hulu Rokan (PHR) and contributes 25% to Indonesia's total oil production. The Central Gathering Station (CGS) “X” at PT PHR utilizes shell and tube heat exchangers (HEX) to effectively heat produced fluids, thereby enhancing the separation of crude oil. Despite their utility, several challenges—such as uneven fluid distribution, fouling, and tube plugging—have compromised the performance of heat exchangers (HEX). These issues can result in some units failing to reach the desired temperature. This study assessed the performance of HEX at CGS X using Aspen HYSYS and Aspen Exchanger Design and Rating (EDR) software, concentrating on key parameters including the heat transfer coefficient, pressure drop, and fluid velocity. The analysis revealed that low fluid velocity within the shell increased the risk of fouling, and a fouling resistance exceeding 0.03 ℉·hr·ft²/Btu significantly diminished efficiency. To address this, a redesigned heat exchanger (HEX) was proposed to optimize fluid velocity, achieving a rate of 1.15 ft/s. This adjustment reduced fouling and enhanced heat transfer while maintaining economic feasibility by decreasing the required heat transfer area. Operational recommendations based on the performance evaluation included making appropriate fluid distribution adjustments and conducting timely maintenance to ensure reliable operation